2020
DOI: 10.3390/w12123460
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical Characteristics and Irrigation Suitability Evaluation of Groundwater with Different Degrees of Seawater Intrusion

Abstract: Groundwater in coastal aquifers is often affected by seawater intrusion, resulting in water quality deterioration. Using groundwater influenced by seawater intrusion for irrigation can lead to crop failure, erosion of machinery and pipes, and adverse effects on farming. In this study, the results of water testing, methods of statistical analysis, ion ratios, a Piper diagram, and a variety of groundwater irrigation suitability models were used to analyze the chemical composition of groundwater and the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
3
1
Order By: Relevance
“…This might be as a result of their proximity to the river bank as WHO [31] reported that both calcium and magnesium which are usually highly soluble in water could be leached from the environment into ground and surface water; again, these metals alongside their carbonates sulphates and chlorides are also known to cause temporary and permanent hardness of water. Meanwhile, values obtained were below the recommended limit of 75-200mg/l for calcium and 30-150mg/l for magnesium recommended by WHO [26] for drinking water as well as the 183.75 mg/l and 91.30 mg/l average values for calcium and magnesium respectively reported by Xu et al [32].…”
Section: Ravi and Krishna (1996) Standard Ratio: <1 Indicates Saltwat...contrasting
confidence: 59%
“…This might be as a result of their proximity to the river bank as WHO [31] reported that both calcium and magnesium which are usually highly soluble in water could be leached from the environment into ground and surface water; again, these metals alongside their carbonates sulphates and chlorides are also known to cause temporary and permanent hardness of water. Meanwhile, values obtained were below the recommended limit of 75-200mg/l for calcium and 30-150mg/l for magnesium recommended by WHO [26] for drinking water as well as the 183.75 mg/l and 91.30 mg/l average values for calcium and magnesium respectively reported by Xu et al [32].…”
Section: Ravi and Krishna (1996) Standard Ratio: <1 Indicates Saltwat...contrasting
confidence: 59%
“…Groundwater is a mixed solution with a complex chemical composition. Through detailed statistics and analysis of its composition, it is possible not only to determine the source of groundwater but also to understand the process of its formation [25]. During the evolution of groundwater, specific ionic components and ratios show certain regular changes.…”
Section: Methodsmentioning
confidence: 99%
“…Salinity Distribution of Regional Groundwater. Conductivity, total dissolved solids (TDS), and Cl − concentration can be used to determine SWI [57]. In this study, Cl − concentration was chosen as the standard classification, and the results (Figure 7) indicated that the 49 water samples from Zhejiang Province comprised 22 freshwater samples, 22 brackish water samples, and 5 saline water samples; 35 freshwater samples, 5 brackish water samples, and 9 saline water samples in Fujian Province.…”
Section: Cai = CLmentioning
confidence: 99%